Importance of three-dimensional geometric analysis in the assessment of the athlete's heart - Schiros, C. G.; Ahmed, M. I.; Sanagala, T.; Zha, W.; McGiffin, D. C.; Bamman, M. M.; Gupta, H.; Lloyd, S. G.; Denney, T. S.; Dell'Italia, L. J. (The American Journal of Cardiology, 2013)
How the left ventricle remodels in response to a high-volume stimulus is important in evaluating the endurance athlete's heart. Marathoners and patients with isolated, moderate chronic compensated mitral regurgitation (MR) represent physiologic and pathologic forms of eccentric left ventricular (LV) remodeling in response to intermittent and chronic volume overload, respectively. Thus, in this study, magnetic resonance imaging with tissue tagging and 3-dimensional data analysis at rest were performed in 19 marathoners (mean age 39 ± 10 years, 47% women), 17 patients with isolated MR without coronary artery disease or medical therapy (mean age 46 ± 5 years, 53% women), and 24 controls (mean age 45 ± 8 years, 50% women). Marathoners and patients with MR had approximately 35% greater LV end-diastolic volume indexes, approximately 50% greater end-systolic volume indexes, and approximately 34% greater LV stroke volume indexes (p <0.0001) compared to controls. However, marathoners` hearts had increased long-axis length, while those of patients with MR did not differ from the hearts of controls. The hearts of patients with MR had greater LV global and apex sphericity compared to those of marathoners and controls (p <0.0001). Marathoners had normal LV mass/volume ratios and wall thicknesses, whereas these were significantly decreased in the MR group. In marathoners, the baseline LV work rate was similar to that in controls and higher in patients with MR compared to controls. In conclusion, marathoners` hearts achieve elevated stroke volume at rest with adherence to an elliptical shape defined by 3-dimensional geometry and mass/volume ratio. Thus, a comprehensive evaluation of LV geometry and mass/volume ratio may be important in the evaluation of the athlete`s heart.